Commercial Agent as a Self-Employed Intermediary : A Gloss to the Judgment of the CJEU of 21 November 2018 in Case 452/17, Zako SPRL v. Sanidel SA - Bucior, Dariusz (Review of European and Comparative Law (Online), 2025)
According to Article 1(2) of Directive 86/653, only a self-employed intermediary can be considered a commercial agent. The first and only judgment of the CJEU that deals with the interpretation of the condition of self-employment is the judgment of November 21, 2018, in Case 452/17, Zako SPRL v. Sanidel SA. In this judgment, the CJEU pointed to some general guidelines on how to assess self-employment (independence) and assumed that the premise of self-employment (independence) also applies to intermediaries who are legal persons. The gloss positively assessed the CJEU’s indication that the assessment of self-employment (independence) should be made taking into account all the circumstances of the case, which seems to confirm that, in the CJEU’s opinion, the typological method should be applied in this respect. There is also no doubt about the specific criteria indicated by the CJEU, such as the extent to which the intermediary is subject to the principal’s instructions, the degree of freedom in organizing his activities, the degree of economic risk, and the method of calculating the remuneration. It can be assumed that the CJEU correctly took the view that it is the personal independence of the intermediary that matters, not economic independence. What raises the most doubts is the assumption that the condition of self-employment (independence) also applies to intermediaries that are legal persons. The meaning of the term “self-employed” and systemic argumentation (referring to the TFEU provisions on the freedom of establishment) justify the view that, according to the legislator’s intention, the self-employment (independence) requirement was to apply only to natural persons. The position of the CJEU that this requirement also applies to legal persons has no functional justification (legal persons cannot be employees). In addition, it unnecessarily hinders the application of the regulations on agency agreements.